Impact of Fermented Soy Beverages Containing Selected Vaginal Probiotics on the In Vitro Fecal Microbiota of Post-Menopausal Women - Margherita D’Alessandro; Davide Gottardi; Silvia Arboleya; Guadalupe Monserrat Alvarado-Jasso; Carola Parolin; Beatrice Vitali; Rosalba Lanciotti; Miguel Gueimonde; Francesca Patrignani (Foods)
The gut microbiome of women can change after menopause, and during this phase women can also be more susceptible to vaginal dysbiosis. Recent studies have explored the probiotic potential of Lactobacillus crispatus BC4 and Lactobacillus gasseri BC9 against various pathogens and their use as co-starters in foods. However, their effects on the gut microbiota of post-menopausal women, who are more prone to dysbiosis, have not been examined. This study investigated the effects of predigested soy beverages (INFOGEST) containing BC4 and BC9 (encapsulated or not) on the composition and metabolic activity of the gut microbiota in post-menopausal women, using a fecal batch culture model. Parameters such as pH, gas, SCFAs, and microbiota composition (targeted qPCR and 16S rRNA gene sequencing) were assessed. The study, while highlighting a strong variability among donors, showed differences in gut microbiota response to the tested products. For instance, donor 2 showed a significant increase in bifidobacteria with BC4 + BC9 and E-BC9, while BC4 increased Ruminococcaceae in donors 1 and 3, and E-BC4 and E-BC9 enhanced Akkermansia in donor 1. BC4, E-BC4, E-BC9, and E-BC4 + BC9 significantly impacted metabolic activity, as measured by SCFAs, compared to other samples. However, no significant differences in gas production were observed.